(untitled) - Harahap, Mara B; Manurung, Sondang R; Marbun, Mas A.; Mihardi, Satria (Advances in Social Sciences Research Journal, 2016)
The aims of this study to analyze the science process skills that students are taught by inquiry training model better than students who use conventional learning. The research method is a quasi-experimental design with non-equivalent pretest-posttest Groups Experimental Design. Experimental class with inquiry learning model training and control class with direct learning model of instruction. The instrument used was a test of skill for science process skills. Data was analyzed using one way ANOVA. The results showed that science process skills that students are taught by inquiry training model better than students who use conventional learning. Inquiry learning in the classroom with Inquiry Training which requires the active involvement of the students can improve learning achievement and attitudes of children to lessons, especially the ability of understanding and communication students. Learning process with Inquiry Training Model able to create the basics of scientific thinking on students, so in this learning process students are learning themselves, develop creativity in solving problems and improving science process skills. Students actually placed as the subject of learning, the role of teachers in teaching with inquiry training is as mentors and facilitators.